Shiʿi Materiality Beyond Karbala : Religion That Matters - Marei, Fouad Gehad, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2024)
This book examines material and multi-sensorial expressions of ShiÊ¿i Islam in diverse, and understudied demographic and geographic contexts.It engages with conceptual debates and makes several propositions that push the frontiers of scholarship on Islamic and Religious Studies, Material Religion, Heritage Studies, and Anthropology and Sociology of Religion.The contributions presented in this volume demonstrate how material things and less thing-like materialities make the praesentia and potentia of the Sacred tangible, how they cultivate intimate relations between human and more-than-human beings, and how they act as links and gateways to the Elsewhere and Otherworldly. The volume posits that materialities of religion are integral to processes of heritagization shaped by competing social and political actors involved in the construction and canonization of religiousâ€"in this case, ShiÊ¿iâ€"heritage.